Genetic Background Matters: Population-Based Studies in Model Organisms for Translational Research - Cubillos-Riffo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
We are all similar but a bit different. These differences are partially due to variations in our genomes and are related to the heterogeneity of symptoms and responses to treatments that patients exhibit. Most animal studies are performed in one single strain with one manipulation. However, due to the lack of variability, therapies are not always reproducible when treatments are translated to humans. Panels of already sequenced organisms are valuable tools for mimicking human phenotypic heterogeneities and gene mapping. This review summarizes the current knowledge of mouse, fly, and yeast panels with insightful applications for translational research. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.